Duplication of Right Testicular Vein: Embryological and Clinical Consideration- A Case Report - Abraham, Joseph (J Clin Diagn Res, 2015)
The testis is the organ upon which the survival of the human species depends. Abnormalities of testicular vessels may lead to loss of gametogenesis and hormone production. The gonadal veins are anatomically asymmetric and there are several anatomical variations involving them. In present case, a variation in draining pattern of right gonadal vein was observed during a routine dissection done at Department of Anatomy. Duplication of right gonadal vein near the point of drainage was found. One of the veins was draining in inferior vena cava and other into right renal vein. According to the reviewed literature, a case like this was rarely reported. There was no other vascular abnormality in this case. Variation in gonadal veins remains unnoticed clinically, but these variations are incidental findings during autopsy and surgeries. The presence of such variations can increase risk of varicocoele and infertility in patients.